Association between Biomarkers of Low-grade Inflammation and Sex Hormones in Women with Polycystic Ovary Syndrome - Hatziagelaki, Erifili; Pergialiotis, Vasilios; Kannenberg, Julia M.; Trakakis, Eftihios; Tsiavou, Anastasia; Markgraf, Daniel F.; Carstensen-Kirberg, Maren; Pacini, Giovanni; Roden, Michael; Dimitriadis, George; Herder, Christian (Experimental and Clinical Endocrinology & Diabetes, 2019)
Objective Women with polycystic ovary syndrome (PCOS) have higher circulating levels of C-reactive protein, but the relationship between inflammation and endocrine function in PCOS remains poorly understood. Thus, this study aimed to investigate the association between low-grade inflammation and sex hormones in women with PCOS.Design and Patients A comprehensive panel of biomarkers of inflammation was measured in serum of 63 women with PCOS using proximity extension assay technology. Associations of 65 biomarkers with sex hormones were assessed without and with adjustment for age and body mass index (BMI).Results In the unadjusted analysis, 20 biomarkers were positively correlated with 17-OH-progesterone (17-OH-P), 14 with prolactin and 6 with free testosterone, whereas inverse associations were found for 16 biomarkers with sex hormone-binding globulin (SHBG), 6 with luteinizing hormone (LH) and 6 with estrogen (all p<0.05). Among the positive associations, correlations were mainly found for five chemokines (CXCL11, CCL4, MCP-4/CCL13, CXCL5, CXCL6) and for VEGF-A, LAP-TGFβ1, TNFSF14 and MMP-1. Inverse associations with sex hormones were mainly present for two chemokines (CXCL1, MCP-2/CCL8), CDCP1, CST5 and CSF-1. Adjustment for age and BMI reduced the number of biomarker associations for SHBG and estrogen, but had hardly any impact on associations with 17-OH-P, prolactin, free testosterone and LH.Conclusion Women with PCOS feature BMI-independent associations between biomarkers of inflammation and certain sex steroid and hypophyseal hormones. Most of these inflammation-related biomarkers were chemokines, which may be relevant as potential mediators of the increased cardiometabolic risk of women with PCOS.
Keywords: inflammation; chemokines; sex hormones; polycystic ovary syndrome; cardiometabolic risk